Self-sustained all-electric wave energy converter system. Issue 5 (26th August 2014) - Sjolte, Jonas; Tjensvoll, Gaute; Molinas, Marta
Abstract : Purpose: – The purpose of this paper is to describe the design and function of Fred. Olsen's wave energy converter (WEC) system Lifesaver with special focus on the stand-alone electrical system that is implemented for operation without grid-connection. Design/methodology/approach: – The paper focus on the detailed design of the DC-Link system that drives the industrial 400 VAC inverters and generators for the production system. The DC-Link is stabilized by an ultra capacitor bank and has no external source or grid-connection. Findings: – The system has been tested through extensive sea trials since April 2012 and has proved its function. Some results from real sea testing are presented. Practical implications: – This paper proves the viability of the specified design and may serve as a basis for the design if similar systems in the future. Originality/value: – This paper presents a WEC system that has proven successful operation through practical tests, and is therefore regarded as a high-value paper as there is limited experience on this subject.